Religious Orientation and Religious Internalization in Madrasa and College Students - Awan, Iram; Hussain , Shaukat (South Asian Journal of Social Sciences and Humanities, 2021)
The research was aimed at examining the relationship between religious orientation (extrinsic,  intrinsic and quest religious orientation) with religious internalization (Introjection religious  internalization and identification religious internalization). A stratified convenient sample of 200  students was selected from different madrasas and colleges of Jhang and Faisalabad. For religious  orientation adopted Urdu version of Religious Orientation Scale developed by Francis & Leslie  (2007) and for religious internalization adopted Urdu version of Religious Internalization Scale  developed by Ryan, Rigby, and King (1993) were used. The extrinsic religious orientation  contributed significantly positive with introjection religious internalization and significantly  negative with Identification Religious Internalization. Intrinsic religious orientation contributed  significantly positive with Identification Religious Internalization and non-significantly negative  with Introjection Religious Orientation. Quest Religious Orientation contributed significantly  positive with Introjection Religious Internalization and non-significantly positive with  identification religious internalization. These two groups namely the madrasa students and college  students when compared on these dimensions it was found that college students have significantly  higher scores on intrinsic religious orientation, extrinsic religious orientation, quest religious  orientation, introjection religious internalization and non-significant differences on identification  religious internalization. The findings of the current study are quite new in Pakistan and are  important in understanding development of religiosity in the students of two competitive  educational systems of madrasa and colleges.
Keywords: Religious orientation; religious internalization; Madrasas students; Colleges students